2012
DOI: 10.1074/jbc.m111.337865
|View full text |Cite
|
Sign up to set email alerts
|

PDZ Domain-containing 1 (PDZK1) Protein Regulates Phospholipase C-β3 (PLC-β3)-specific Activation of Somatostatin by Forming a Ternary Complex with PLC-β3 and Somatostatin Receptors

Abstract: Background:The four PLC-␤ subtypes (␤1-␤4) have different roles in GPCR-mediated signaling despite having similar structures and regulatory modes. Results: PDZK1 mediates the physical coupling of PLC-␤3 to SSTRs using different PDZ domains. Conclusion: PLC-␤3 is specifically involved in SSTR-mediated signaling via its interaction with PDZK1. Significance: The subtype-specific role of PLC-␤ is mediated by differential interactions with PDZ proteins and GPCRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 64 publications
(64 reference statements)
1
21
0
Order By: Relevance
“…Nevertheless, PDZK1 has been implicated in regulating a subset of GPCRs. PDZK1 promotes the formation of a complex between SSTRs and PLCb3, similar to what is observed for LPA 2 R (Oh et al, 2004;Choi et al, 2010), thereby facilitating somatostatinstimulated PLC activation, Ca 21 mobilization, and ERK1/2 phosphorylation (Kim et al, 2012). PDZK1 also functions to enhance human prostacyclin receptor (hIPR) cell surface localization and cAMP signaling and contributes to endothelial cell migration and angiogenesis (Turner et al, 2011).…”
Section: Membrane-associated Guanylate Kinase With Inverted Orientatimentioning
confidence: 68%
“…Nevertheless, PDZK1 has been implicated in regulating a subset of GPCRs. PDZK1 promotes the formation of a complex between SSTRs and PLCb3, similar to what is observed for LPA 2 R (Oh et al, 2004;Choi et al, 2010), thereby facilitating somatostatinstimulated PLC activation, Ca 21 mobilization, and ERK1/2 phosphorylation (Kim et al, 2012). PDZK1 also functions to enhance human prostacyclin receptor (hIPR) cell surface localization and cAMP signaling and contributes to endothelial cell migration and angiogenesis (Turner et al, 2011).…”
Section: Membrane-associated Guanylate Kinase With Inverted Orientatimentioning
confidence: 68%
“…RERG was reported as a prognostic marker in breast cancer, whose expression correlated inversely proliferation, patient survival, and development of distant metastases (48). It has been reported that PDZK1 forms a complex linking somatostatin receptors and phospholipase C-b (PLC-b), necessary for somatostatin physiologic responses (49). Although further studies are warranted, epigenetic silencing of RDBP in metastatic PPGL may cause global changes in chromatin and/or gene transcription, possibly affecting expression of genes (e.g., JUNB, PDZK1, RERG, GPX3) involved with response to apoptotic stimuli and invasion, proliferation, and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…PDZK1 belongs to the family of Na + /H + exchange regulatory factors which comprises four members: NHERF1-4 with NHERF3 also known as PDZK1. NHERFs have been reported to regulate the function of several GPCRs including the parathyroid 1 receptor, somatostatin receptors 1-5 (SSTRs), human prostacyclin receptor (hIPR), β 2 -adrenergic receptor (β 2 AR), metabotropic glutamate receptor 5, purinergic P2Y1 receptor, CCR5 chemokine receptor and κ opioid receptor [29,[42][43][44][45][46]. CRFR1 and the 5-HT 2A R represent the fourth and fifth GPCRs that have been shown to interact with PDZK1.…”
Section: Discussionmentioning
confidence: 99%